MYCOBACTERIUM TUBERCULOSIS VIRULENCE - B. I. Vishnevskiy; O. A. Manicheva; P. K. Yablonskiy (Инфекция и иммунитет, 2015)
This review presents recent data on the genetic determinants and the virulence factors of Mycobacterium tuberculosis (MBT). The mechanisms of adaptation of the pathogen in the host organism and alterative manifestations are described as well as the relationship of virulence, drug resistance and the genetic affiliation of MBT are analyzed in thearticle. It was demonstrated the clinical and prognostic significance of Mycobacterium tuberculosis virulence. The cyclic changes in MBT virulence coincide with the rise and fall of the incidence of tuberculosis has been established. Some virulence factors are targets to create fundamentally new anti-TB drugs.